The Integration of Augmented Reality in Blended Culture-Based English Language Learning - Umisara, Elinda; Sunarsih, Diah; Hidayah, Siti Ulin Nuril (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study examines the integration of Augmented Reality (AR) technology in English language learning based on blended culture. The research addresses two key questions: 1) How does the use of AR learning media influence student engagement in blended culture-based English learning? 2) How does the use of AR learning media affect students' understanding in blended culture-based English learning? The researcher employs a mixed-method approach with a quasi-experimental and qualitative descriptive design, involving two schools with a total sample of 60 students and 4 teachers selected through convenience sampling. Data were collected through observations and interviews to obtain qualitative data. Surveys and tests were used to gather quantitative data. The results show that: 1) student engagement increased, particularly in active participation, interaction with AR media, and collaboration with peers. 2) AR significantly enhances student engagement and understanding, with post-test scores increasing from 56.33 to 80.33 in School A and from 49.33 to 85.00 in School B. Survey results indicate that using AR technology in English learning enriches students' understanding of cultural diversity. AR allows students to engage more deeply in exploring local and target cultures, such as through interactive visualizations and culturally relevant contexts in the learning materials. This study highlights the significant potential of AR as an effective tool for enhancing the quality of English language learning through a blended culture-based approach.